Making sense of risky haredi behaviors in israel during the covid-19 pandemic - BELDER, FERİT (My University, 2022)
Covid-19 not only posed a threat to the bodies of individuals or their mental health but also disrupted routines that are re-producing certain communities every day. This is particularly the case for communities with already securitized identities such as the ultra-Orthodox (Haredi) society in Israel. Its authentic narrative, routines and practices that had been sustained thanks to their decades-long autonomy within the state, faced a substantial challenge when the state-led pandemic measures arrived in Haredi towns. This article seeks to explain the Haredi non-compliance with certain pandemic instructions like closing religious and educational centers, through the conceptual lens of an ontological security approach. It argues that the ontological security concerns of the Haredi leadership hampered them from fully complying with the state-led pandemic measures, even at the of the lives of individual Haredim.

Covid-19 sadece bireylerin fiziki ve zihinsel sağlıklarına tehdit oluşturmakla kalmamış aynı zamanda bazı toplulukları her gün yeniden üreten rutinleri kesintiye uğratmıştır. Bu durum, İsrail’deki ultra-Ortodoks (Haredi) toplumu gibi halihazırda güvenlikleştirilmiş kimliklere sahip topluluklar için özellikle geçerlidir. Haredilerin devlet içerisinde sahip oldukları on yıllar süren özerklikleri sayesinde sürdürülen özgün anlatı, rutin ve pratikler, devlet kaynaklı pandemi önlemleri Haredi şehirlere ulaştığı zaman ciddi bir meydan okumayla karşılaşmıştır. Bu makale, din ve eğitim merkezlerinin kapatılması gibi belirli pandemi önlemlerine Haredi itaatsizliğini ontolojik güvenlik yaklaşımı çerçevesinde açıklama amacındadır. Makale, Haredi liderliğin ontolojik güvenlik endişelerinin kendilerini, bireysel olarak Haredilerin hayatlarını riske atma pahasına, devlet kaynaklı pandemi önlemlerine uymaktan alıkoyduğunu iddia etmektedir
Covid-19 pandemisi döneminde israil’deki riskli haredi davranışlarını anlamlandırmak
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Siyaset Bilimi; Uluslararası İlişkiler; Social Sciences and Humanities; Sociology; Political Science; International Relations; ULUSLARARASI İLİŞKİLER; Sosyal Bilimler Genel; Sosyal Bilimler (SOC); INTERNATIONAL RELATIONS; SOCIAL SCIENCES, GENERAL; Social Sciences (SOC); General Social Sciences; Social Sciences & Humanities; Haredim; Ontological Security; Anxiety; Fear; Autonomy; ONTOLOGICAL SECURITY; WORLD-POLITICS; IDENTITY; ANXIETY; Harediler; Ontolojik Güvenlik; Endişe; Korku; Özerklik; Haredim; Ontological Security; Anxiety; Fear; Autonomy